“Slavic Enlightenment”: Functioning of Cyrilo-Methodian tradition in modern Bulgarian culture - Джевиецка, Евелина (Poznańskie Studia Slawistyczne, 2018)
The article raises the question of functioning of Cyrilo-Methodian tradition in the Bulgarian culture in the conditions of modernity. The subject of analysis is the traditional and originally religious notion of the “Slavic / Bulgarian enlighteners”. It is argued that Cyril and Methodius are presented as patrons of enlightenment, first understood as education, and then as an historical epoch, and that is why they become absolute role models of a citizen, a Bulgarian, an Orthodox, a communist. The conclusion is that the starting point for understanding the modern narrative about the creators of Slavic alphabet should be the idea of enlightenment, which in the course of time has been secularized and concretized.